Plan de capacitación y orientación en turismo sostenible a los visitantes de la ciudad de Santa Marta (2021)
This research seeks to create in the hands of tourism service providers and tourists, all as agents of change, strategies and improvement plans in order to solve the negative impact that we have brought as consumers to our department of Magdalena and our city of Santa Marta or at least minimize them as much as possible, and thus bring a true change to the ecological image of the department compared to other tourist destinations in the country, and leave a practical guide for tourist training, with this project we seek to sow a positive citizen awareness in favor of the care and preservation of the environment, through nature tourism. In this way, we will not only have a sustainable and ecologically great destination, but we will also be a destination worth visiting in the face of our competition.